Inter-day reliability of a Wattbike cycle ergometer sprint protocol in male rugby players - Cushman, S.; Bott, R.; Twist, C.; Highton, J. (Journal of Trainology, 2018)
Objective: The purpose of this study was to establish the inter-day reliability of several performance variables measured during a 2 × 6 s sprint on a Wattbike cycle ergometer in male rugby players. Reliablilty was assessed against an `analytical goal` of detecting meaningful changes that might be expected with fatigue in rugby. Design & Methods: Sixteen male rugby players performed three trials of the protocol on different days seperated by a mimimum of 48 h. The protocol comprised 2 × 6 s `all out` cycle sprints with 90 s recovery between efforts. Typical error (TE), coefficient of variation (CV), smallest worthwhile change (SWC) and moderate change (MC) were calculated between each trial for seven variables. Results: Peak Power output significantly increased from the first to the third trial (3.3-4.4 %), whilst all variables had better reliability from trials 2-3 than 1-2. Mean power (3.7%), peak power (4.2%) and total distance (2.7%) had a CV% lower than dec rements observed with team sport fatigue (~5%), however only total work had a TE (2.1 kJ) lower than the smallest worthwhile change (4.6 kJ) while the remainder were lower than the moderate worthwhile change. Conclusion: Assuming one complete habituation trial is completed, total work appears to be the most reliable variable capable of detecting a worthwhile change in performance. We recommend using this variable to monitor fatigue in rugby players.